The discovery of male Potiicoara brasiliensis (Crustacea, Spelaeogriphacea) with notes on biology and distribution - Pires-Vanin, Ana Maria S. (Zootaxa, 2012)
The male of Potiicoara brasiliensis is reported for the first time with evidence of sexual dimorphism. Male diagnosticcharacters are described and compared with the other three species of Spelaeogriphidae. Males present differential mor-phology on both distal podomere articles of the antennula and antenna, an elongate and curved bare endopod on pleopod2, a pair of short round penes on the sternum near the base of pereopod 7, and telson with dorsum almost smooth and apexstraight. Material is sampled for the first time from karstic areas north of the species type-locality, Gruta Ricardo Franconear Corumbá City, and Gruta do Curupira in the Araras Mountains. These new findings expand the distribution of thespecies over seven hundred kilometers. Comparisons between exemplars of both sexes are presented. A hypothesis on the distributional pattern of P. brasiliensis is introduced based on the geological history of Central-West Brazil.